The Role of School Principal’s Transformation Leadership in Developing the Adiwiyata Program: A Case Study of SMP Negeri Gabus, Grobogan Regency - Rina Nurhayati; Rosalina Br Ginting; Muhtarom (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to describe the role of transformational leadership of the school principal in developing the Adiwiyata (eco-school) program at SMP Negeri 1 Gabus, Grobogan Regency. The research employed a qualitative descriptive approach through observation, interviews, and documentation involving the principal, teachers, and students as key informants. Data were analyzed using an interactive model that includes data reduction, data display, and conclusion drawing to reveal how transformational leadership dimensions contribute to environmental education and school sustainability. The findings indicate that the principal’s transformational leadership plays a crucial role in realizing an environmentally conscious school culture. Through idealized influence, the principal becomes a role model who embodies environmental values and integrates them into the school’s vision and policy. Inspirational motivation fosters collective enthusiasm and active participation of teachers and students in environmental programs. Intellectual stimulation encourages creativity and innovation through initiatives such as digital waste banks and eco-brick projects. Meanwhile, individualized consideration is reflected in personalized guidance and empowerment that enhance teachers’ confidence and engagement. Overall, transformational leadership has significantly strengthened environmental policy, increased school-wide participation, and shaped sustainable ecological behavior. The study provides new empirical evidence that transformational leadership effectively drives cultural transformation toward green, participatory, and innovative school management.